2019
DOI: 10.3390/su11071932
|View full text |Cite
|
Sign up to set email alerts
|

Hospitals’ Financial Health in Rural and Urban Areas in Poland: Does It Ensure Sustainability?

Abstract: Literature review suggests that rural hospitals are in the worst financial conditions due to several factors: They are smaller, located in remote areas, and they provide less specialized services due to their problems with employing well-qualified staff. We decided to check whether it is true in the case of Polish hospitals. Based on the literature review, we have assumed that rural hospitals have less favorable financial conditions. In order to verify this assumption, we use seven indicators of financial heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…It is their responsibility to decide whether to leave the emergency area and go to a safer place. However, upon arrival at the scene of the State Fire Service, the chief commander of the rescue operation is the most senior and experienced firefighter and becomes the Rescue Leader [15]. The Rescue Leader has to carry out detailed reconnaissance of the scene of the incident, to calculate the forces and means at one's disposal, and to decide whether these forces are sufficient or whether additional assistance needs to be called for.…”
Section: Hospital Safety -Legal Liabilitymentioning
confidence: 99%
“…It is their responsibility to decide whether to leave the emergency area and go to a safer place. However, upon arrival at the scene of the State Fire Service, the chief commander of the rescue operation is the most senior and experienced firefighter and becomes the Rescue Leader [15]. The Rescue Leader has to carry out detailed reconnaissance of the scene of the incident, to calculate the forces and means at one's disposal, and to decide whether these forces are sufficient or whether additional assistance needs to be called for.…”
Section: Hospital Safety -Legal Liabilitymentioning
confidence: 99%
“…Michalski et al (2018) develop a model to find the optimal level of debt for nonprofit organisation environmental conditions. Bem et al (2019) find that in the case of Polish hospitals there is no difference in financial condition between rural and urban hospitals. Dziuba et al (2019) examine the use of the Internet by older adults in Poland and their result suggests that older adults are becoming more digital.…”
Section: Introductionmentioning
confidence: 71%
“…European countries implemented a decentralized maternity services in order to ensure good access to necessary care independent of a mother's place of residence [34]. Moreover, recent research have shown that type of hospital is not the main determinant of hospital financial performance in Europe [35].…”
Section: Perinatal Regionalizationmentioning
confidence: 99%